Etika Komunikasi Dalam Ruang Media Massa: Analisis Framing Pemberitaan LGBT di Media Lokal Jambi - Eka Muchamad Taufani; Herri Novealdi; Andeka Widodo (Jurnal Ilmiah Dikdaya, 2023)
The phenomenon of the presence of LGBT groups in Indonesia has been discussed for a long time. Marked by the emergence of the first openly gay organization, namely Lambda Indonesia on March 1, 1982, since then until now LGBT groups have tried to show their existence in the public space. This is done as an effort so that their existence can be accepted and recognized in society. The objective of this research is to describe how online media in Jambi Province positions LGBT news. And knowing the framing and application of ethics in reporting on LGBT. The research was conducted using qualitative methods with library research by exploring theories and their relationships or with the influence between each variable sourced from books, journals, and others, both offline in the library, and obtained online from the internet. During the period June-September 2022, Tribunjambi.com reported a lot about the Erayani case. There are 103 stories published by this media by taking various reporting perspectives. Jambi Independent in total there are 12 stories that have been published on their media portal. Jambi Update Online Media contains 12 news stories. Metrojambi.com contains 18 news published by Metrojambi.com until September 1, 2022. Meanwhile, Jambina.com only contains one news. The report was published on June 21, 2022. In framing the news on the LGBT case regarding the Erayani case, both online media Tribunjambi.com, Jambi Independent, Metrojambi.com, Jambi Update, and Jambina.com are not much different.